Chimica e Sostenibilità: un gioco da ragazzi! - Deganello, Francesca; Testa, Maria Luisa; Zanelli, Alberto; Riccardo Lucentini, Riccardo; Ienco, Andrea; Calamante, Massimo; Vineis, Claudia; Varesano, Alessio; Armida Torreggiani, Armida (Chimica nella Scuola, 2024)
Thanks to a collaborative network of CNR Institutes located throughout Italy, created as part of the project Change the Game: Playing to prepare for the challenges of a sustainable society, a number of playful-educational activities concerning the teaching of science and sustainability at elementary school have been designed, developed and successfully tested. Indeed, it has been shown how play fosters interest in the topic addressed and develops the child’s problem-solving and critical thinking aptitude. In this paper, four play-educational paths related to chemistry and sustainability are proposed entitled “Touch, Contact, Chemistry and Sustainability”, “The Recycling Game”, “Discovering Animal Fibers”, and “The Colors of Energy”.